Environmentally assisted cracking of a single crystal nickel-based superalloy - Dawson, Karl; Duarte Martinez, Fabian; Gray, Simon; Nicholls, John R.; Gibson, Grant J.; Leggett, Jonathan; Tatlock, Gordon J. (Taylor & Francis, 2023)
Single crystal material, of CMSX-4® alloy composition, was cast and secondary orientation was controlled at the machining stage, to produce c-ring cross-section tubes with known crystallographic orientations. The c-ring tubes were coated with NaCl before being subject to loading up to 700MPa and heated for durations of up to 2 hrs at 550°C in flowing environments containing air and SO2. No cracking was observed in short term tests that were run in the absence of either NaCl, or SO2, indicating a symbiotic interaction is required to initiate cracking. Experiments confirm the presence of oxygen, chlorine and sulphur at the crack tips, formed along {001} crystallographic planes, however, they were distributed discretely, with several oxide and sulphide phases observed. In this work, we image, analyse and identify the phases formed during the cracking and corrosion of CMSX-4® superalloy and hypothesise on the complex chemical interactions that take place during crack initiation.
Keywords: single crystal nickel superalloy; environmentally assisted cracking